Learning curve for endorectal ultrasound in young and elderly: lights and shades - Surace, Alessandra (Open Med (Wars), 2016)
Aim of the study is to highlight difficulties faced by an inexperienced surgeon in approaching endorectal-ultrasound, trying to define when learning curve can be considered complete. A prospective analysis was conducted on endorectal-ultrasound performed for subperitoneal rectal adenocarcinoma staging in the period from January 2008 to July 2013, reported by a single surgeon of Department of Oncology, Section of General Surgery, “San Luigi Gonzaga” Teaching Hospital, Orbassano (Turin, Italy); the surgeon had no previous experience in endorectal-ultrasound. Fourty-six endorectal-ultrasounds were divided into two groups: early group (composed by 23 endorectal-ultrasounds, made from January 2008 to May 2009) and late group (composed by 23 endorectal-ultrasound, carried out from June 2009 to July 2013). In our experience, the importance of a learning curve is evident for T staging, but no statystical significance is reached for results deal with N stage. We can conclude that ultrasound evaluation of anorectal and perirectal tissues is technically challenging and requires a long learning curve. Our learning curve can not be closed down, at least for N parameter.